2008
DOI: 10.1007/s00520-007-0400-2
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of tropisetron on ECG parameters in cancer patients

Abstract: In this study, tropisetron did not show any ventricular and atrial arrhythmogenic effect because of repolarization abnormalities. Only it may cause a slight decrease in heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…In two studies conducted on oral dolasetron, PR, QTc, and QRS prolongations were detected [21,22]. Yavas et al, in their study on tropisetron (5 mg), another 5-HT 3 antagonist, showed sinusal bradycardia at the 30th minute [17]. Most of these studies used anthracycline or its derivatives.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In two studies conducted on oral dolasetron, PR, QTc, and QRS prolongations were detected [21,22]. Yavas et al, in their study on tropisetron (5 mg), another 5-HT 3 antagonist, showed sinusal bradycardia at the 30th minute [17]. Most of these studies used anthracycline or its derivatives.…”
Section: Discussionmentioning
confidence: 94%
“…The adverse effects of 5-HT 3 antagonists such as dolasetron, ondansetron, granisetron, and tropisetron were studied by several authors [2,9,10,17]. Several studies were conducted on healthy individuals on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate testing for Her2 aims to ensure that every patient who might benefit from trastuzumab receives appropriate treatment, and that costly and potentially cardiotoxic trastuzumab4042 is not given to patients with non-overexpressing tumours. Inconsistencies in the sensitivity of IHC Her2 testing have been attributed to the use of different antibodies, differences in tissue fixation and IHC reagents, antigen retrieval methods and interobserver variability 3 43 44…”
Section: Discussionmentioning
confidence: 99%
“…However, several trials suggested tropisetron and granisetron had few, if not any, side effects on QT interval [54,56]. Palonosetron has recently become available commercially and the QT prolongation risk has not been recorded by the Arizona CERT.…”
Section: Anti-emetic Drugsmentioning
confidence: 97%
“…In regards to the risk of QT interval prolongation, serotonin-receptor antagonists have also been shown to block human potassium and sodium channels, thereby causing potential QT interval prolongation [56]. However, several trials suggested tropisetron and granisetron had few, if not any, side effects on QT interval [54,56].…”
Section: Anti-emetic Drugsmentioning
confidence: 98%